2023
DOI: 10.1002/advs.202205237
|View full text |Cite
|
Sign up to set email alerts
|

Room Temperature Viscous Flow of Amorphous Silica Induced by Electron Beam Irradiation

Abstract: The increasing use of oxide glasses in high‐tech applications illustrates the demand of novel engineering techniques on nano‐ and microscale. Due to the high viscosity of oxide glasses at room temperature, shaping operations are usually performed at temperatures close or beyond the point of glass transition Tg. Those treatments, however, are global and affect the whole component. It is known from the literature that electron irradiation facilitates the viscous flow of amorphous silica near room temperature for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…We have shown that a-Al 2 O 3 plasticity extends to the microscale, but a profound question still remains: why does a-SiO 2 , the prototypic glass former, remain brittle? Although a-SiO 2 shows a considerable amount of ductility on the nano and microscale, the literature indicates that it can be considered mainly as anomalous behavior, e.g., plasticity has been observed in the presence of an electron beam, [34,46] the simulated atom structure is artificially densified before straining to allow plasticity, [47] or the plasticity in micropillar compression is caused by the small sample volume and the compressive stress delays crack propagation, and at the latest the fracture typically occurs once the load is released. [22,31] No experimental data on a-SiO 2 micropillars larger than D > 3.1 μm tested under ambient conditions have been published to our knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that a-Al 2 O 3 plasticity extends to the microscale, but a profound question still remains: why does a-SiO 2 , the prototypic glass former, remain brittle? Although a-SiO 2 shows a considerable amount of ductility on the nano and microscale, the literature indicates that it can be considered mainly as anomalous behavior, e.g., plasticity has been observed in the presence of an electron beam, [34,46] the simulated atom structure is artificially densified before straining to allow plasticity, [47] or the plasticity in micropillar compression is caused by the small sample volume and the compressive stress delays crack propagation, and at the latest the fracture typically occurs once the load is released. [22,31] No experimental data on a-SiO 2 micropillars larger than D > 3.1 μm tested under ambient conditions have been published to our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the presence of a strong enough electron beam can induce artificial plasticity in mechanical experiments. [46,55] We performed dedicated experiments to study the effect that our SEM electron beam setup has on our micropillar samples during mechanical loading (see Section S13, Supporting Information). No significant difference was found in the mechanical behavior between the a-Al 2 O 3 micropillar samples strained with electron beam On or Off.…”
Section: Discussionmentioning
confidence: 99%
“…The scale bars are for 200 nm (see open acce reference [25] for details). (III) Micro-pillar compression of silica glasses under a 20 kV and an 1 A/m 2 electron beam at three stages: (a) before, (b) during and (c) after compression (see open acce reference [26] for details).…”
Section: Indiamentioning
confidence: 99%
“…Table 1 provides approximate oxide compositions of both ABS glasses used worldwide and NAP glasses which were The analysis of the effects of self-irradiation resulting from the decay of nuclear waste radionuclides is among the tasks of researchers investigating the long-term behaviour of vitrified HLW. Indeed, the role of self-irradiation in the behaviour of nuclear waste glasses is not fully understood with partly controversial results [8,22,23] and even unexpected radiation-induced effects reported on glasses irradiated externally by electrons [24][25][26]. Figure 1 demonstrates the radiation-induced fluidisation termed also quasi-melting with the drop of glass viscosity from that characteristic to solids to that one characteristic to the liquid state of matter as reported for tens of nano- [27], hundreds of nano- [25], and micro-metre [26]-sized glass samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation